PENETAPAN PUSAT PERTANGGUNGJAWABAN UNIT-UNIT PENDAPATAN PADA BISNIS RUMAH SAKIT - Widarto, Widarto (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
Title: [The Determination of Responsibility Center of Revenue Units on Hospital Business]The purpose of starting a business is the goal of economic and social objectives. In the economic profit goals into measurement tools are easy to do. To measure the success of the hospital business is supported by profit income units, so the determination of income units will be important in determining the responsibility center of management. By that way the hospital business and the number of units of income are so complexity, the hospital management to collect revenue from sources Outpatient, Inpatient, Support Unit and also others. Income units that occur in outpatient covering the ER, Poly and specialists, delivery room, operating room and physiotherapy. While there are general in inpatient wards, maternal ward, pediatric ward, ICU, NICU and ICCU. In the supporting unit no pharmacy, laboratory, radiology, laundry, sterileyzation and hem dialysis. Other units there are cafeterias, parking lots and incinerators.